Bird and bat mortality at short, monopole cell towers in Rock Creek Park, Washington, D.C., USA - Stephanie D. Dickey; J. Edward Gates; Bradley Dickey; Ken Ferebee (Wildlife Society Bulletin)
Abstract Bird and bat mortality resulting from collisions with manmade towers is well‐documented, and our understanding of this phenomenon is increasing, particularly for taller structures (≥61 m) with guy wires and the obstruction lighting required by the U.S. Federal Aviation Administration. However, shorter, monopole tower designs remain underinvestigated. We report the results of a 3‐year study (2006–2008) on the effects of 2 existing telecommunication (“cell phone”) towers on migratory bird and bat mortality in Rock Creek Park (ROCR), Washington, D.C., USA. The towers in ROCR are the shorter (30.9 m and 39.6 m in ht), monopole design and lack obstruction lighting and guy wires. We conducted mortality surveys on a daily basis during spring and autumn migrations, and conducted weekly surveys during the summer. Bird carcasses were collected, but we were unable to attribute any avian or bat mortality to the towers at these sites. © 2012 The Wildlife Society.